Determinación teórica y experimental de permeabilidades relativas de tres fases - Edgar Ricardo Pérez Carrillo; Jorge Rojas; Nicolás Santos Santos (Revista Fuentes El Reventón Energético, 2007)
An improved experimental apparatus for measurement of three phases relative permeability, using three phase acoustic separator was made in the ICP¿s special core laboratory. The improvement was aimed at two objectives: to modify the equipment in order to obtain more reliable experimental data and to interpret them appropriately. Special emphasis was laid upon pressure drop oscillations and uncertainties in oil, gas and water saturation. This paper also presents a critical review of experimental and theoretical developments in the area of three phase relative permeability